(untitled) (Al-Academy, 2022)
This study revolves around the rapid changes of science and a comparison of the formal and practical aspects and the reason behind summoning the changes and their types, which are subject to the influence of the recipient. This transformation represents formal and intellectual production cycles and formal functional generation that is subject to the goals of the system of multiple differences at the level of time and place. It meets the needs and the request for change, but access to it comes through multiple systems and portals that are different from the normal and the usual, so this study was called (meta and its dimensions in the designed biological formation (virtual reality environment - a model). The research seeks to find solutions in multiple aspects of life to realize the environmental environment of man His world and a new contemporary life line line the reception systems that are undergoing change and transformation.